The effect of time-intervals in characterizing price-related uncertainties in techno-economic analysis. (20th December 2022) - Gupta, Ajay; Williams, Eric; Gaustad, Gabrielle
Highlights: Single sample Monte Carlo inflates price-driven uncertainty. Time-interval of historical data used significantly affects uncertainty outcomes. Understanding price uncertainty requires knowledge of purchase/sales frequency. Dynamic sampling Monte Carlo could offer simple alternate uncertainty analysis. Analysts should use conservative assumptions on shorter time-intervals.